The impact of internal audit quality, effective internal controls, and institutional context factors on local government performance in Nigeria - Usang, Obal Usang Edet (2016)
As the third tier of government in Nigeria, local governments are struggling with issues bothering on performance failures. Stakeholders are demanding answers on why local governments are unable to deliver on their mandate. Accountability mechanisms like internal audit and internal controls have been acknowledged to bring about improvement in processes and performance. However, there seem to be little influence of these mechanisms as performance failures still trail local governments. It has also been acknowledged that internal audit and internal controls alone may not generate the much needed improvement unless embedded in the governance system of an organization. On this basis, this study examined the impact of internal audit quality, effective internal controls, and institutional context factors on local government performance in Nigeria. Data were collected from 301 heads of internal audit units of local governments in Nigeria using a structured questionnaire. Also, follow up interviews were conducted to clarify the findings of the survey. The results indicated that internal audit quality and effective internal controls were positively and significantly related to local government performance. Also, institutional context factors showed mixed relationships with local government performance. Particularly, strategic planning and top management commitment were positively and significantly related to performance. However, internal audit and external audit collaboration and political interference were negatively and significantly related to local government performance while strategic mission, regulations, internal audit relationship with management and auditees, and corporate ethical culture had no significant relationship with performance. Thus, the study provides evidence of a relationship between internal audit quality, effective internal controls, institutional context factors and performance in the local government. Therefore, there is need for local administrators and policy makers to address institutional context issues to enable internal audit quality and effective internal controls thrive for better performance of local governments in Nigeria.